Kesetaraan Gender Kemal At Tarturk Dalam Negara Turki Republik - Khusna, Zakiyatul; Firdausi, Jamilatur; Zakariah, Irfan; Wasil, Moch (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
This research aims to analyze the thoughts and updates made by Kemal at Tarturk on gender equality in the Turkish Republic. This research uses a literature study method of works related to Kemal Attarturk. This research uses historical research methods with a gender approach that serves as a tool for analyzing gender equality in Kemal at Tarturk's government policies. Kemal was the first President of the Republic of Turkey, he had Westernization thoughts, Kemal was born in Salonika in 1881. Women in the late 20th century period in the Ottoman Turkish Sultanate still received conservative treatment in society. Kemal's policy of gender equality in women greatly changed the life of a woman, Kemal gave freedom of emancipation, revised marriage laws, and ensured women's equal rights in matters of inheritance and divorce. In addition, Kemal also increased women's access to education and gave them the right to vote, thus opening up opportunities for them to participate in various field. Keywords: Policy, Gender Equality, Kemal Ataturk, Republic of Turkey, Government